2020
DOI: 10.3390/su12145802
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Analysis of the Contributions of Co-Located Industrial Symbiosis to Achieve Sustainable Development in an Industrial Park in Northern Spain

Abstract: Resource efficiency is a strategy with great potential to make progress towards the UN Sustainable Development Goals (SDGs), since it can contribute to meeting a variety of economic, environmental and social targets. In this context, this investigation developed a systemic analysis of co-located Industrial Symbiosis (IS) synergies in an industrial park formed of four companies. To this end, public data showing that the main activity in this park concerned materials, water and steam flows were supported with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Diverse studies have been developed from the perspective of relating the role of industrial symbiosis, SDGs, and sustainable development [18,21,22]. Perhaps one of the most relevant contributions on this topic is a part of the work promoted by Schroeder et al [18].…”
Section: Sustainable Development Sdgs and Industrial Symbiosismentioning
confidence: 99%
“…Diverse studies have been developed from the perspective of relating the role of industrial symbiosis, SDGs, and sustainable development [18,21,22]. Perhaps one of the most relevant contributions on this topic is a part of the work promoted by Schroeder et al [18].…”
Section: Sustainable Development Sdgs and Industrial Symbiosismentioning
confidence: 99%
“…A case of industrial symbiosis (IS) in Spain was analyzed by Ruiz-Puente and Jato-Espino. They concluded that the changes implemented in industrial parks resulted equated to contributions to nine SDGs and fourteen of their specific targets, proving the domino effect associated with the application of IS policies by governments and public entities [19].…”
mentioning
confidence: 99%